Język edukacji szkolnej w integracyjnym modelu wsparcia ucznia z doświadczeniem migracji w rodzinie - Małgorzata Pamuła-Behrens (Postscriptum Polonistyczne)
The number of students with migrant experiences at Polish schools is increasing. This group includes both foreign students and Polish students coming back from emigration together with their parents. They receive educational support in order to facilitate their adaptation and integration. Those students are taught how to communicate at school and study in Polish, which means that they are taught the language of school education. Teaching the language of school education can be located in between foreign language didactics and native language didactics. The article describes the relation between teaching Polish as a language of school education and teaching Polish as a foreign language. The most important aspect of teaching a foreign language is to prepare a learner to communicate in everyday life and professional life situations. Efficiency is essential here; language correctness is of secondary importance. The most important element in the process of teaching the language of education is to develop the language skills that will enable a student to communicate at school, gain new knowledge and use it effectively. It requires different educational content, teaching methodology and requirements. The article presents the reflection on teaching the language of education with reference to the Polish educational system.